2010
DOI: 10.1007/s12078-010-9080-2
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Expectation: The Effect of Assuming Homogeneity on Drink Perception

Abstract: Here, we investigate whether the expectation that a drink tastes consistent across mouthfuls influences reported taste. A paradigm was developed to prompt the expectation that drink stimuli tasted identical to each other. Participants sipped two drinks and indicated whether they tasted the same. In some trials, the drinks appeared to be poured from the same jug, prompting the homogeneous taste expectation. These 'same-jug' drink pairs were reported more similar than 'different-jug' drink pairs, where the drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 57 publications
3
28
1
Order By: Relevance
“…These results are all the more remarkable given that the participants in experiment 2 knew that what they were drinking was actually always the same drink (tasted from the same glass) in each of the three rooms that they visited. Thus, one would have expected there might, if anything, have been an assumption of continuity (or unity) in people's minds that would have worked against any change in subjective ratings that were, in fact, obtained [32]. Second, the results outlined here also support the conclusion that people's feelings about the environment in which they happen to be tasting/drinking whisky can carry over to influence their feelings about the drink itself.…”
Section: Discussionsupporting
confidence: 62%
“…These results are all the more remarkable given that the participants in experiment 2 knew that what they were drinking was actually always the same drink (tasted from the same glass) in each of the three rooms that they visited. Thus, one would have expected there might, if anything, have been an assumption of continuity (or unity) in people's minds that would have worked against any change in subjective ratings that were, in fact, obtained [32]. Second, the results outlined here also support the conclusion that people's feelings about the environment in which they happen to be tasting/drinking whisky can carry over to influence their feelings about the drink itself.…”
Section: Discussionsupporting
confidence: 62%
“…[17,36]). Especially relevant here are findings from [47]. These researchers demonstrated that there appears to be a 'unity assumption' when it comes to flavour perception.…”
Section: Music's Influence On the Sensory Aspects Of Winementioning
confidence: 82%
“…Nevertheless, related work from the food industry has stressed the importance of the initial tasting experience, given the assumption of homogeneity (of a given food product), across a particular tasting experience (e.g. see [104][105][106][107]). …”
Section: Layering Tasting Sensationsmentioning
confidence: 99%